Modelagem molecular comparativa e estudos de acoplamento molecular da enzima lanosterol 14alfa - desmetilase do Moniliophthora perniciosa - Pacheco, Alessandra Gomes Marques (2010)
The cultivation of cocoa was extremely important for the Brazilian economy but it has been hampered by the witches' broom disease, caused by the Moniliophthora perniciosa. The lack of efficient control measures resulted in lower production, changes in land use, property sales, reduction of jobs and damage to the environment. An important strategy to develop control methods the is broom disease witch is to study the interactions of lanosterol 14α- desmethylase of M. perniciosa enzyme with known fungicides, thereby aiming at the design of new bioactive molecules that block the biosynthesis of ergosterol and consequently, induce the death of the fungus. Azole compounds are active both in vitro and in situ against M. perniciosa, yet there is no systematic study on the interaction of these compounds against the enzyme lanosterol 14- demethylase this pathogen. It’s study created a model for the lanosterol 14α-demethylase enzyme of M. perniciosa using comparative molecular modeling. Subsequently the catalytic site was characterized in terms of physico-chemical and molecular docking studies. From the results we present a proposal of pharmacophore model that helps to understand the interactions of the azole compound with its molecular target. However, only the biological evaluation of new compounds will identify a consensus model that accounts for the chemical properties essential for inhibition of M. perniciosa.